1994
DOI: 10.1029/94jc00712
|View full text |Cite
|
Sign up to set email alerts
|

Circulation of Prince William Sound, Alaska

Abstract: The circulation of Prince William Sound, Alaska, is described using hydrographic (1974–1989), current meter (1977–1979), and acoustic Doppler current profiler (1986–1990) observations from both the sound and the adjacent Gulf of Alaska. Ancillary data include data for winds, freshwater runoff, and satellite‐tracked drifters. Prince William Sound is a small inland sea in that it is wide enough to have appreciable horizontal cyclonic circulation. It is also a fjord in that it has basin depths to 700 m but is sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
76
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 85 publications
(79 citation statements)
references
References 9 publications
3
76
0
Order By: Relevance
“…The red circle delineates the single station (PWS2) that was sampled during every survey of PWS from 2009 through 2012. surface layer (Niebauer et al, 1994;Musgrave et al, 2013;Halverson et al, 2012b;Vaughan et al, 2001). Downwellingfavorable winds, which dominate from September through May, drive surface flow into PWS through Hinchinbrook Entrance, with compensatory outflow through Montague Strait (Niebauer et al, 1994;Halverson et al, 2012a). This "flowthrough" scenario is reduced and more complex between May and September, when winds are only weakly downwelling favorable or upwelling favorable and surface flows are typically weaker with reversals through either strait becoming more common (Halverson et al, 2012a;Niebauer et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The red circle delineates the single station (PWS2) that was sampled during every survey of PWS from 2009 through 2012. surface layer (Niebauer et al, 1994;Musgrave et al, 2013;Halverson et al, 2012b;Vaughan et al, 2001). Downwellingfavorable winds, which dominate from September through May, drive surface flow into PWS through Hinchinbrook Entrance, with compensatory outflow through Montague Strait (Niebauer et al, 1994;Halverson et al, 2012a). This "flowthrough" scenario is reduced and more complex between May and September, when winds are only weakly downwelling favorable or upwelling favorable and surface flows are typically weaker with reversals through either strait becoming more common (Halverson et al, 2012a;Niebauer et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…This observation has only been made once, and we speculate that this is related to the synchronicity between when our measurements were collected and when downwelling conditions abated on the shelf. Being that deep water renewal events occur during nondownwelling periods (Niebauer et al, 1994) and can flush bottom waters in as rapidly as a month (Halverson et al, 2012a), calcite undersaturation could build up during stagnant winter months in the deepest portions of PWS but be extinguished by the time our survey takes place in May given this is the time seasonal downwelling conditions are on the decline (Mathis et al, 2014b;Weingartner, 2007). Yearto-year differences in downwelling forcing on the shelf can be large (Mathis et al, 2014b), and likely determine if calcite undersaturation is observed given our set cruise schedule.…”
Section: Far-field Influence Of Glacial Meltmentioning
confidence: 99%
See 3 more Smart Citations